Análise da interação intraguilda entre duas espécies de peixes predadoras e suas influencias sobre uma comunidade de peixes em meio experimental - Marques, Rafael da Silva (2019)
.Introductions of non-native animal or plant species occur in all regions known to man, and population growth and intensification of economic activities are some of the phenomena that eventually increase the introduction rates of such species. Within this panorama, competitive relations and predation have promoted great effects on local communities. Thus, the present work aimed at understanding the effect of top predators, exotic and native, in a community of fish, as well as their effects of interspecific and intraspecific interaction in the experimental environment. Based on the result it was possible to observe that in the analysis of the intraspecific competition performance between the treatments containing the native species Pseudoplatystoma corruscans, and the exotic species Clarias gariepinus, the native species obtained a higher average weight gain, going against the data of the literature, which most often points to exotic species as more efficient in terms of survival, feeding and performance. The result also demonstrated a high degree of dietary overlap between treatments, as well as the feeding preference of P. corruscans for Oreochromis niloticus and C. gariepinus for Astyanax altiparanae